Enemies or Learning Partners? The Interplay of Power and Learning in a Cross Boundary Work Group - Marjorie H. Carkhuff (Adult Education Research Conference, 1999)
This study investigated power relationships in a cross boundary health care work group. The study found that power within groups is more fluid and flexible than previous studies suggested. Factors that influence power levels and their impact on learning are discussed